Analysis of Consumer Perceptions of Financial Transparency in Insurance Product Marketing Practices in Indonesia - Pertiwi, R Dewi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study examines how Indonesian consumers perceive financial transparency in insurance product marketing and how it impacts trust and loyalty. It explores the role of cultural, religious, and financial literacy factors in shaping these perceptions, offering insights into the broader dynamics of consumer behavior. Using a systematic literature review approach, the research analyzes secondary data from previous studies on transparency, trust, and insurance marketing. The findings indicate that clear and accessible communication about policy terms, costs, and benefits positively influences trust. When transparency aligns with cultural and religious expectations, it significantly enhances loyalty. The study also highlights that consumers with higher financial literacy are more critical in assessing transparency, while those with lower literacy tend to rely more on trust. The results support the hypothesis that transparency fosters trust and long-term loyalty within the insurance industry. Practical implications suggest that insurance companies, particularly in emerging markets like Indonesia, should prioritize transparent communication strategies that align with consumers’ cultural and religious values to build competitive advantages. Future research should explore transparency across different regions and the role of digital tools in enhancing transparency.